Differences in breast-feeding initiation and continuation by maternal diabetes status - Oza-Frank, Reena; Chertok, Ilana; Bartley, Adam (Public health nutrition, 2015)
To examine (i) the prevalence of and associations between breast-feeding initiation and continuation by maternal diabetes status and (ii) the reasons for not initiating and/or continuing breast-feeding by maternal diabetes status. Secondary data analyses of a population-based cross-sectional study were conducting using data from the US Centers for Disease Control and Prevention's Pregnancy Risk Assessment Monitoring System (PRAMS), 2009-2011. Multivariable logistic regression was used to investigate the associations between breast-feeding initiation and continuation by diabetes status. Thirty states and New York City, USA. Mothers of recently live-born infants, selected by birth certificate sampling. Among 72755 women, 8.8 % had gestational diabetes mellitus (GDM) and 1.7 % had pregestational diabetes mellitus (PDM). Breast-feeding initiation was similar among GDM and no diabetes mellitus (NDM) women (80.8 % v. 82.2 %, respectively, P=0.2), but continuation was lower among GDM (65.7 % v. 68.8 %, respectively, P=0.01). PDM women had lower initiation and continuation compared with NDM (78.2 %, P=0.03 and 60.4 %, P<0.01, respectively). In adjusted analyses, current smoking status was a significant effect modifier for initiation, but not for continuation. Differences in breast-feeding initiation and continuation prevalence by maternal diabetes status may reflect differences in prenatal education, indicating the need for increased efforts among PDM women. Additionally, non-smoking women with PDM or GDM would benefit from additional breast-feeding education.